2021
DOI: 10.51253/pafmj.v71isuppl-1.2404
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Reference Interval of Liver Function Tests During Pregnancy in Urban Area of District Rawalpindi Pakistan

Abstract: Objective: To determine the reference Interval of liver function tests during uncomplicated pregnancy inpopulation of Rawalpindi and assess their correlation over first and second trimesters of pregnancy. Study Design: Cross sectional study. Place and Duration of Study: Department of Chemical Pathology & Endocrinology Armed Forces Institute ofPathology Rawalpindi from Feb 2017 to Jun 2018. Methodology: Seven hundred and fifty four pregnant women with uncomplicated, single intrauterine pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The results of the study indicated that the reference intervals for bilirubin, albumin, ALP, and ALT in the first trimester included: bilirubin 3–9 μmol/L, albumin 31–45, ALT 3–35 and ALP 122–224 U/L. In the second trimester, bilirubin, 2–7 μmol/L, albumin, 28–45 g/L, and ALT 1–33U/L, and 131–300U/L ( 19 ).…”
Section: Discussionmentioning
confidence: 97%
“…The results of the study indicated that the reference intervals for bilirubin, albumin, ALP, and ALT in the first trimester included: bilirubin 3–9 μmol/L, albumin 31–45, ALT 3–35 and ALP 122–224 U/L. In the second trimester, bilirubin, 2–7 μmol/L, albumin, 28–45 g/L, and ALT 1–33U/L, and 131–300U/L ( 19 ).…”
Section: Discussionmentioning
confidence: 97%